DETERMINAN NILAI PERUSAHAAN SEKTOR ANEKA INDUSTRI DI BURSA EFEK INDONESIA - Mutia Rahmawati (2021)
The research was conducted with the aim of knowing whether the Capital Structure measured using Debt to Equity Ratio (DER), Liquidity measured using Current Ratio (CR), and Profitability measured using Return On Equity (ROE) have an influence on Firm Value as measured using Price to Book Value (PBV ). The population of this research is various industrial sector companies listed on the the Indonesia Stock Exchange (IDX) in 2016-2019. The technique used to select the sample is purposive sampling method so that there are 20 companies that meet the criteria with a 4 year period, so the total sample is 80 samples. Data analysis in research was assisted by Microsoft Excel 2010, while hypothesis testing with panel data regression analysis used Eviews version 11 with a significance level of 5%. This study obtained the results, namely: (1) Capital Structure has a positive and significant effect on Firm Value, (2) Liquidity has no and insignificant effect on Firm Value, (3) Profitability has a positive and significant effect on Firm Value. Keywords : Capital Structure, Liquidity, Profitability and Firm Value.